Opportunity versus necessity entrepreneurship: Two components of business creation - Robert W. Fairlie; Frank M. Fossen (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
A common finding in the entrepreneurship literature is that business creation increases in recessions. This counter-cyclical pattern is examined by separating business creation into two components: "opportunity" and "necessity" entrepreneurship. Although there is general agreement in the previous literature on the conceptual distinction between these two factors driving entrepreneurship, there are many challenges to creating a definition that is both objective and empirically feasible. We propose an operational definition of opportunity versus necessity entrepreneurship using readily available nationally representative data. We create a distinction between the two types of entrepreneurship based on the entrepreneur's prior work status that is consistent with the standard theoretical economic model of entrepreneurship. Using this definition we document that "opportunity" entrepreneurship is pro-cyclical and "necessity" entrepreneurship is counter-cyclical. We also find that "opportunity" vs. "necessity" entrepreneurship is associated with the creation of more growth-oriented businesses. The operational distinction proposed here may be useful for future research in entrepreneurship.
Keywords: 330